2013
DOI: 10.1590/s2317-64312013000400018
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de voz e qualidade de vida após laringectomia supracricóide

Abstract: OBJETIVO: Avaliar sujeitos submetidos a laringectomia supracricóide quanto à autoavaliação da voz, análises perceptivo-auditiva e acústica e impacto da alteração vocal na qualidade de vida. MÉTODOS: Estudo prospectivo, observacional, que envolveu 12 sujeitos do gênero masculino, com disfonia orgânica, média de idade de 59,3 anos, que realizaram laringectomia supracricóide para exérese de neoplasia maligna de laringe. Foi realizada análise perceptivo-auditiva, por meio da escala GRBASI em duplo-cego. A análise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies confirmed the tendency of patients with dysphonia to assess their own voice as being of good quality after a partial laryngectomy (23) . One must take into account other factors that may be influencing such self-concept since laryngectomy surgeries, partial and total, severely alter the laryngeal structure, or remove part of the organ, jeopardizing the vocal quality intensively, or leading patients to seek for substitutive phonation with esophageal speech, tracheoesophageal prosthesis, etc.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies confirmed the tendency of patients with dysphonia to assess their own voice as being of good quality after a partial laryngectomy (23) . One must take into account other factors that may be influencing such self-concept since laryngectomy surgeries, partial and total, severely alter the laryngeal structure, or remove part of the organ, jeopardizing the vocal quality intensively, or leading patients to seek for substitutive phonation with esophageal speech, tracheoesophageal prosthesis, etc.…”
Section: Discussionmentioning
confidence: 76%
“…Chemoradiotherapy treatment can cause a number of problems that can affect swallowing (4,10,13) , causing individuals to adapt their diet in a way that allows them to eat effectively, supplying their nutritional needs. However, in the present study, it was noted that only one individual follows a diet considered normal (Table 1) It is believed that since the study included only individuals who had already finished their treatment with chemoradiotherapy, they were already adapted to the dietary modifications demonstrated in the questionnaire, which were imposed by their condition and, therefore, there was no correlation between the results of SWAL-QOL and chemotherapy and radiotherapy sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In Oliveira, Augusti, Smith's work (2013) 37 , which was conducted with subjects who underwent surgery debated the dynamics phonation and the glottal competence in COPD.…”
Section: Discussionmentioning
confidence: 99%